2017
DOI: 10.1371/journal.pone.0174865
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide profiling in oral squamous cell carcinoma identifies a four genetic marker signature of prognostic significance

Abstract: BackgroundCancers of the oral cavity are primarily oral squamous cell carcinomas (OSCCs). Many of the OSCCs present at late stages with an exceptionally poor prognosis. A probable limitation in management of patients with OSCC lies in the insufficient knowledge pertaining to the linkage between copy number alterations in OSCC and oral tumourigenesis thereby resulting in an inability to deliver targeted therapy.ObjectivesThe current study aimed to identify copy number alterations (CNAs) in OSCC using array comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 40 publications
3
13
0
2
Order By: Relevance
“…Recently, LTBP3 has been identified as one of a number of genes with copy number alterations in patients with oral squamous cell carcinomas. 52 The data from our orthotopic murine model for head and neck cancer employing HEp-3 epidermoid carcinoma cells ( Figure 6 ) indicated that expression of LTBP-3 is important for the levels of spontaneous metastasis of cancer cells from primary buccal tumors to lungs, but not for late stages of metastatic colonization associated with vascular arrest, survival, extravasation and lung colonization, all of which follow the intravasation step.…”
Section: Resultsmentioning
confidence: 91%
“…Recently, LTBP3 has been identified as one of a number of genes with copy number alterations in patients with oral squamous cell carcinomas. 52 The data from our orthotopic murine model for head and neck cancer employing HEp-3 epidermoid carcinoma cells ( Figure 6 ) indicated that expression of LTBP-3 is important for the levels of spontaneous metastasis of cancer cells from primary buccal tumors to lungs, but not for late stages of metastatic colonization associated with vascular arrest, survival, extravasation and lung colonization, all of which follow the intravasation step.…”
Section: Resultsmentioning
confidence: 91%
“…Amplification of this region of 11q has been previously reported in HNSCC patients and shown to be correlated with worse outcomes. 8,9 Furthermore, alterations of CCND1 and/or cyclin-dependent kinase inhibitor 2A (CDKN2A) (both leading to deregulation of the G1/S cell cycle checkpoint pathway), were strongly associated with rapid engraftment.…”
mentioning
confidence: 99%
“…Loss in FHIT and RB1 were the only well described HNSCC associated mutations (25) detected in TADE and which were absent from both the tumor and NE, suggesting this TADE is an independent clone and not related to the tumor. Interestingly, the size of a loss on 3p26.3 in NE that increased in this TADE would be important to investigate further for possible role in early genetic event in the NE, since a loss in this region has been suggested to be an independent prognostic factor in OSCC patients (26,27).…”
Section: Genetic Alterations Reveal Both Intratumoral Clonal Heterogementioning
confidence: 99%
“…Surprisingly, one of the genetic events-loss and/or LOH of 3p21.3-was common in all the five NE. Inactivating mutations in this region have been a consistent finding in cancers, especially HNSCC, and have been associated with early development of dysplastic lesions in HNSCC (13,27,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The clinical significance of this genetic event in NE is unknown and warrants further investigation.…”
Section: Normal Epithelium (Ne)mentioning
confidence: 99%